Analisis Keselamatan dan Kesehatan Kerja dengan Metode JSA dan HAZOPS - Budiman, Anang (Jurnal Teknologi, 2024)
This research was motivated by the problem of work accidents among workshop employees, including exposure to sparks, legs being hit by production items and iron fences, sore eyes and blistered hands. And welding employees do not use PPE when working. The aim of the research is to identify hazards and risks that can cause work accidents in CV. XYZ uses the Job Safety Analysis (JSA) method. Analyzing the level of risk by assessing likelihood (possibility) and consequence (severity) using the Hazard and Operability Study (HAZOPS) method at CV. XYZ. And provide recommendations for improvements to very high and high risk levels. The type of data in this research is primary data. Primary data obtained directly from the field, namely potential hazard data obtained by making direct observations at CV. XYZ. The results of the research have found that workers' attitudes towards work have a high level of risk and potential danger which is then classified into sources of danger that have extreme, high, medium and low risk. The proposed improvements given to overcome these dangers include providing personal protective equipment, conducting safety and health training for workers to get workers who are professional and understand the importance of occupational health and safety.